Soil erosion estimation in lowland agricultural areas using universal soil loss (USLE) - A case in Felda Jengka 15, Pahang / Khairi Khalid and Elias Mohd Den - Khalid, Khairi; Mohd Den, Elias (2004)
This short treatise is a small attempt to estimate the amount of soil erosion annually for a lowland agricultural area in FELDA Jengka 15, Pahang, employing a widely used mathematical formulation for soil erosion, the USLE. The contributing area under studies is around 1574.84 hectares and this is quite a sensible area in order to derive a suitable and sound indication for its erosion problems. On the other hand, this is particularly important from a management side since it reflects how effective FELDA handles the erosion problems. The value the annual loss computed for three stages under due considerations; the site clearing (phase I), earthwork activities (phase II) as well as the planting stage (phase III) indicated that the erosion problems are generally temporary and found to be more severed during site clearing and earthworks prior to the re-establishment of the vegetations. These values (4.78/0.57/0.17 tons/hectare/year) for phase I, II and III respectively also gave us an indication that the study area falls under a low category soil loss (Agricultural Department).